Analisis Pola Sebaran Populasi Serta Alasan Pembudidayaan Burung Jenis Kelamin Betina: Stusi Kasus Burung Murai Batu Piaraan Di Kota Bengkulu. - Putranto, Heri Dwi; Brata, Bieng; Sutriyono, Sutriyono; Nurmeilisari, Nurmeilisari; Indriani, Dinda (BPFP Universitas Bengkulu, 2024)
Until recently, keeping white-rumped shama bird as a pet is still a favorite option for Indonesia bird lovers. Study results showed that most bird breeders keep male birds, and the female population remains unknown. However, bird keeping and breeding efforts still require the existence of female birds as important parental factor. This research aims to analyze population distribution patterns and determine the reasons of breeder and bird lovers for cultivating female white-rumped shama. The location was determined purposively in Bengkulu City. Data was collected by snowball sampling method using questionnaire with respondent interview system in the field. Distribution pattern data was analyzed using the Variance Mean Ratio formula, while research data on reasons for cultivation were tabulated and analyzed descriptively. The results showed that the VMR value for the distribution pattern of the female white-rumped shama population was 7.55 and was classified as group distribution pattern. The reason for cultivating female white-rumped shama in Bengkulu city were economic value/profit (64% of respondents), followed by the reason for pleasure (36% of respondents). It can be concluded that most breeders' reason to keep white-rumped shama was for economic profit.